Implementation Of Legal Protection For Victims Of Body Shaming On Social Media - Syam, Andi Fatmawati; Nasir, Citra; Ichsan, Nursyamsi (Innovative: Journal Of Social Science Research, 2022)
Indonesia as a state of law must provide legal protection for its citizens, by paying attention to current technological developments, where many criminal acts occur in the form of body shaming on social media which is currently a phenomenon, where someone easily insults someone on social media without caring about the material and mental impact felt by the victim. The research method used is normative legal research. The results showed that legal protection for victims of body shaming has not been successfully realised, because in preventive efforts and repressive efforts it has not been able to have a significant effect because we still find in social media there are still many actions like this and sometimes the victims are lazy to extend this problem for various reasons but the danger is if the victim has damaged his mentality because it is repeated. Repressive efforts by law enforcers have not been adequate in providing a deterrent effect and paying more attention to the mental condition of victims during the investigation and investigation process.